2015
DOI: 10.3791/52354
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique for the Implantation of Tissue Engineered Vascular Grafts and Subsequent <em>In Vivo </em>Monitoring

Abstract: The development of Tissue Engineered Vessels (TEVs) is advanced by the ability to routinely and effectively implant TEVs (4-5 mm in diameter) into a large animal model. A step by-step protocol for inter-positional placement of the TEV and real-time digital assessment of the TEV and native carotid arteries is described here. In vivo monitoring is made possible by the implantation of flow probes, catheters and ultrasonic crystals (capable of recording dynamic diameter changes of implanted TEVs and native carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Using SIS with immobilized heparin and VEGF, we developed cell‐free off‐the‐shelf vascular grafts with submillimeter inner diameters (850–900 µm) that were implanted into the arterial system of a mouse. Similar to our previous study with an ovine animal model, grafts demonstrated host cell integration and a confluent endothelium within the lumen (34, 36). Cell‐free vascular grafts of such small sizes are a continuing challenge for the field of tissue engineering.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Using SIS with immobilized heparin and VEGF, we developed cell‐free off‐the‐shelf vascular grafts with submillimeter inner diameters (850–900 µm) that were implanted into the arterial system of a mouse. Similar to our previous study with an ovine animal model, grafts demonstrated host cell integration and a confluent endothelium within the lumen (34, 36). Cell‐free vascular grafts of such small sizes are a continuing challenge for the field of tissue engineering.…”
Section: Discussionsupporting
confidence: 86%
“…One study implanted a heparin‐functionalized elastomer in a rat model that proved to be effective in promoting endothelialization (21). However, heparin‐functionalized grafts occluded within the first few hours after implantation into the carotid artery of sheep (34, 36). On the other hand, in the current study we found no difference in graft patency between heparin‐only (SH) and heparin/VEGF (SHV) grafts using the same biomaterial and immobilization strategy, despite the much smaller graft diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After excising ≈ 5cm in-situ of native carotid in order to retain longitudinal tension, each A-TEV (4cm in length) was placed end to end in the carotid artery using interrupted suture technique. Following the unclamping of the artery and restoration of normal blood flow through the TEV, instruments were placed onto the newly sutured vessel allowing real-time monitoring of arterial dynamics during recovery as described recently[37]. A 4mm doppler flow probe (Transonic Systems Inc., Ithaca NY) was placed proximal to the TEV, 1mm sonomicrometry crystals (Sonometrics Inc., London, Canada), were placed laterally opposite to each other at the midpoint of the A-TEV.…”
Section: Methodsmentioning
confidence: 99%
“…At indicated time points, implanted probes were connected to corresponding transducers to enable data acquisition using Sonolab DS3 (Sonolab version 1.0.0.60, Sonometrics Inc., London, Canada) as previously described[37]. Following transducer calibration and establishment of stable connections, 30sec–1min of data were recorded.…”
Section: Methodsmentioning
confidence: 99%